2014
DOI: 10.1177/2158244014530410
|View full text |Cite
|
Sign up to set email alerts
|

IEP Use by General and Special Education Teachers

Abstract: The role of general and special educators in implementing the Individualized Education Program (IEP) is critical. This study investigated the perceptions of those teachers on when they read the IEP, how they measure attainment of IEP goals and objectives, and the IEPs usefulness in instructional planning. Four hundred twenty-six teachers from suburban school districts in central New Jersey were respondents. Results indicated that the majority of general and special education teachers are reading their students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 25 publications
3
26
0
4
Order By: Relevance
“…In this case, the IEPs prepared would not impact the students for whom they are written. To make qualitative differences in the education of SWD, general education and special education teachers need to use the IEP for instructional planning purposes (Rotter, 2014). Finally, the results of this study demonstrated that there is clearly a need for rubric for evaluating the IEPs in Turkey.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this case, the IEPs prepared would not impact the students for whom they are written. To make qualitative differences in the education of SWD, general education and special education teachers need to use the IEP for instructional planning purposes (Rotter, 2014). Finally, the results of this study demonstrated that there is clearly a need for rubric for evaluating the IEPs in Turkey.…”
Section: Discussionmentioning
confidence: 83%
“…Regarding the IEP as a product, researchers investigated the teachers' perceptions of IEP's effectiveness on children's learning. Rotter (2014) reported that teachers found IEP moderately useful in planning instruction and they implemented the majority of IEP objectives that had positive impact on SWD. However, the excessive amount of IEP goals found in this research implies lack of IEP implementation in schools.…”
Section: Discussionmentioning
confidence: 99%
“…Introduit dans les différents systèmes scolaires occidentaux à partir de 1975, le plan d'intervention (PI) est ainsi devenu une obligation légale dans de nombreux pays (Rotter, 2014;Drasgow et al, 2001). Par exemple, l'Agence européenne pour l'éducation adaptée et inclusive indique que la plupart des pays utilisent un projet éducatif individualisé (PEI) pour les étudiants à besoins éducatifs particuliers (BEP) pendant la scolarité obligatoire.…”
Section: Introductionunclassified
“…In Canada as well as in the United States, the individualized education plan (IEP) constitutes a legal right [4]. The concept of the individualized education plan is not new: this term first appeared in the United States in 1975 with the adoption of the Individuals with Disabilities Education Act (IDEA) which guaranteed access to free public education to meet the needs of every student between the ages of 3 and 21 [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…In special needs education, no document is more important than the intervention plan, as it enables to ensure the application of a program that is both specifically tailored to this particular clientele [8] and fully compliant under the law [4] [9]. "According to American law, the term individualized education program or IEP means a written statement for each child with a disability that is developed, reviewed, and revised in a meeting (…)" (IDEA, 2004, part 300).…”
Section: Introductionmentioning
confidence: 99%